The architecture of "smart factories" - Dmitrieva, Alena (project baikal, 2021)
The article considers the need to develop a fundamentally new concept of industrial architecture – "smart factory". The factors that influence the architectural solutions of contemporary enterprises are listed. The principles of forming the architecture of "smart factories" are formulated and unveiled. Examples of production facilities that meet these principles are given. The conclusion about the positive impact of these principles on the architecture of high-tech industrial facilities is made.